2018
DOI: 10.1002/ejoc.201801519
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Visible‐Light Photocatalytic Tandem Radical Addition–Cyclization Strategy for the Synthesis of Sulfonyl‐Containing Isoquinolinediones

Abstract: A mild radical cascade reaction for the synthesis of sulfonyl‐containing isoquinolinediones has been developed, in which sulfonyl radicals can be accessed from simple sodium sulfinates under visible light and eosin Y catalysis. This tandem approach features a broad range of substrates and functional group tolerance. With this strategy, trifluoromethylated isoquinolinedione was also obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…Subsequently, Zuo et al reported that the eosin-Y catalyzed N -alkyl- N -methacryloyl benzamides with sodium sulfinates under visible light irradiation afforded isoquinoline-1,3(2 H ,4 H )-diones ( Scheme 213B ). 321 Several substituted N -methacryloylbenzamides at different positions of the benzene ring were smoothly reacted with a series of aryl/alkyl sulfinates to produce a wide range of corresponding products in good yields. Sodium trifluoromethanesulfinate was also used, however, the desired trifluoromethylsulfonylation product was not formed.…”
Section: Applications Of Sodium Sulfinatesmentioning
confidence: 99%
“…Subsequently, Zuo et al reported that the eosin-Y catalyzed N -alkyl- N -methacryloyl benzamides with sodium sulfinates under visible light irradiation afforded isoquinoline-1,3(2 H ,4 H )-diones ( Scheme 213B ). 321 Several substituted N -methacryloylbenzamides at different positions of the benzene ring were smoothly reacted with a series of aryl/alkyl sulfinates to produce a wide range of corresponding products in good yields. Sodium trifluoromethanesulfinate was also used, however, the desired trifluoromethylsulfonylation product was not formed.…”
Section: Applications Of Sodium Sulfinatesmentioning
confidence: 99%
“…[273] A similar transformation was carried out photochemically in DMFÀ H 2 O at room temperature under an inert atmosphere applying sodium sulfinates as sulfonyl radicals source (eosin Y served as the photocatalyst). [274] AgNO 3 -or CAN-mediated reaction of o-vinylanilides 522 with sodium sulfinates 523 under an inert atmosphere led to benzoxazines 524 (Scheme 225). [275] Electric current was also used as the oxidant for this transformation.…”
Section: Construction Of Six-membered Heterocyclesmentioning
confidence: 99%
“…The reaction proceeds as a cascade of radical transformations including the generation of the sulfonyl radical, its addition to the terminal double bond, and radical cyclization with the aromatic ring [273] . A similar transformation was carried out photochemically in DMF−H 2 O at room temperature under an inert atmosphere applying sodium sulfinates as sulfonyl radicals source (eosin Y served as the photocatalyst) [274] …”
Section: Sulfonylation Followed By Cyclizationmentioning
confidence: 99%
“…The use of cheap, non-irritating sodium sulfinate opens the way to the possibility to generate sulfonyl radicals by means of visible-light-induced catalysis. Zuo et al disclosed a tandem radical addition/cyclization concept for the synthesis of isoquinolinediones [53]. A mild radical cascade reaction is based on sulfonyl radical generation from the appropriate sodium sulfinate 114 and Eosin Y 11a under blue LED irradiation (Scheme 15a).…”
Section: Application Of Visible-light-mediated Catalysis In Synthementioning
confidence: 99%